Un opúsculo latino sobre el Anticristo: (Ms 9465 B.N.M.) - Jiménez Calvente, Teresa (1999)
MS 9465 of the Spanish National Library contains a short latin text, an Anticrist's biography with all the elements of the Medieval apocalyptic tradition, mixed with moral and exhortative contents. Wholly convinced of the Anticrist's imminent arrival, the anonymous writer encourages all believers to return to the basic principles of the catholic religion, which are also included in this text.
Keywords: Anticristo -- En la literatura